2010
DOI: 10.1097/nrl.0b013e3181a2eace
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Changes in Cerebral Blood Flood Velocities in Depressive Pseudo-Dementia and Alzheimer Disease Patients

Abstract: We have shown that CBFv decreased in patients with AD and DPD, but vasoneuronal activity was only impaired in patients with AD. On the other hand, although the results do not show significant differences between depressive and demented groups by TCD, further studies will be needed for differentiating these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
1
12
0
1
Order By: Relevance
“…Most studies reported no significant differences in resting mean flow velocities between demented and control groups [20, 21, 22, 23, 24, 25, 26, 27, 28], or, lower mean flow velocities in demented groups including AD [29, 30, 31, 32, 33, 34, 35], VaD or multi-infarct dementia [30, 32, 34, 36], regardless of subtype [15]. Mean flow velocity measures in AD and VaD groups appeared similar [18, 24, 30, 32, 34, 36, 37], although this was not always the case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies reported no significant differences in resting mean flow velocities between demented and control groups [20, 21, 22, 23, 24, 25, 26, 27, 28], or, lower mean flow velocities in demented groups including AD [29, 30, 31, 32, 33, 34, 35], VaD or multi-infarct dementia [30, 32, 34, 36], regardless of subtype [15]. Mean flow velocity measures in AD and VaD groups appeared similar [18, 24, 30, 32, 34, 36, 37], although this was not always the case.…”
Section: Resultsmentioning
confidence: 99%
“…Four fTCD studies compared dementia subtypes and controls: two found that individuals with AD had an attenuated response to cognitive demand [35, 52], and two found no differences between AD patients and controls [26, 51]. Matteis et al [51], however, reported that their AD group displayed a reduction in lateralised function, and Asil and Uzuner [26] reported an attenuated response only in their VaD group.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have found significantly lower flow velocities in AD compared to controls (Caamano et al, 1993; Roher et al, 2006, 2011; Sun et al, 2007; Vicenzini et al, 2007; Claassen et al, 2009; Stefani et al, 2009; Gucuyener et al, 2010). The most often studied vessel was the middle cerebral artery (MCA) while other major intracranial arteries were studied less frequently.…”
Section: Transcranial Ultrasound In Admentioning
confidence: 99%
“…The most often decreased velocity in MCA in AD patients compared to healthy controls was the mean flow velocity (Roher et al, 2006, 2011; Vicenzini et al, 2007; Claassen et al, 2009; Stefani et al, 2009), although not all results support these findings (Ries et al, 1993). Decreases in peak systolic and end diastolic velocities varied in different arteries (Caamano et al, 1993; Sun et al, 2007; Gucuyener et al, 2010). According to a large longitudinal study (Ruitenberg et al, 2005), subjects with higher velocities in MCA were less likely to develop AD.…”
Section: Transcranial Ultrasound In Admentioning
confidence: 99%
See 1 more Smart Citation